2022
DOI: 10.3390/ph15111348
|View full text |Cite
|
Sign up to set email alerts
|

In Vitro, Molecular Docking and In Silico ADME/Tox Studies of Emodin and Chrysophanol against Human Colorectal and Cervical Carcinoma

Abstract: Anthraquinones (AQs) are present in foods, dietary supplements, pharmaceuticals, and traditional treatments and have a wide spectrum of pharmacological activities. In the search for anti-cancer drugs, AQ derivatives are an important class. In this study, anthraquinone aglycons chrysophanol (Chr), emodin (EM) and FDA-approved anticancer drug fluorouracil were analyzed by molecular docking studies against receptor molecules caspase-3, apoptosis regulator Bcl-2, TRAF2 and NCK-interacting protein kinase (TNIK) and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(5 citation statements)
references
References 50 publications
0
5
0
Order By: Relevance
“…The presence of six strong hydrogen bonds with tankyrase‐2 transferase (Figure 21) could be one of the major reasons for its selection as an anticancer drug. Uniquely, K9 and S7 also exhibit hydrogen binding interactions (Figures 18, 21), and despite being fewer, they have higher binding energy than capecitabine, which could be attributed to the geometry of the synthesized compound in the active binding pockets of the receptor [53].…”
Section: Resultsmentioning
confidence: 99%
“…The presence of six strong hydrogen bonds with tankyrase‐2 transferase (Figure 21) could be one of the major reasons for its selection as an anticancer drug. Uniquely, K9 and S7 also exhibit hydrogen binding interactions (Figures 18, 21), and despite being fewer, they have higher binding energy than capecitabine, which could be attributed to the geometry of the synthesized compound in the active binding pockets of the receptor [53].…”
Section: Resultsmentioning
confidence: 99%
“…When transposed to an in vivo toxicity study, clear evidence was found that the molecular interaction effect observed in the virtual environment was somewhat similar to that of the biological model [ 86 ]. Furthermore, the transposition of in silico virtual screening of anticancer drugs using the receptors caspase-3, Bcl-2 and TRAF2 and the interaction proteins kinase and cyclin-dependent kinase 2 (CDK2) to an in vitro trial was validated through the in vitro anticancer activity against HCT-116 and the cell line HeLa [ 87 ]. In addition, results from molecular docking studies were crucial for validating the interactions of twenty phytocompounds with high binding affinity for the target receptors AChE, COX2 and MMP8, which are involved in the physiopathology of Alzheimer’s disease.…”
Section: Discussionmentioning
confidence: 99%
“…ADME property analysis proved that the selected four compounds have the ability to be used as drug candidates against the HCT116 cell line. The study of colorectal cancer found that the ADME result predicted the toxicity and pharmacokinetic properties of Emodin and Chrysophanol ( Ahmad et al, 2022 ). In our study, we selected four compounds that had no toxic substance for humans as drug candidates through the ProToxII software, where several studies reported the same result ( Banerjee et al, 2018 ).…”
Section: Discussionmentioning
confidence: 99%